2015
DOI: 10.1111/ijfs.12880
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of fermentation conditions for probiotication of sorghum wort by Lactobacillus acidophilus LA5

Abstract: Probiotics are considered as significant segments of functional foods. The response surface methodology was used to optimise the fermentation process conditions for the development of a probiotic sorghum wort beverage fermented with Lb. acidophilus LA5. The central composite design was applied with three fermentation parameters such as temperature, inoculation dosage and initial pH. Each parameter was varied at three levels. All parameters had single or interaction significant effects (P < 0.05) on the respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…The change of dry cell weight depending on temperature increase for L. brevis ED25 was higher than that of other strains. The study was supported by Simonson, Salovaara, and Korhola (2003) and Hassani, Zarnkow, and Becker (2015) who reported that the bacterial cell concentration increased significantly with the increase of the fermentation temperature. A partial decrease of dry cell weight for L. curvatus N19 was observed after fermentation of 25h and at temperature after 29.5 o C. Similarly, Zhou, Zeng, Han, and Liu (2015) stated that the cell growth rate was significantly influenced by fermentation temperature, but the growth rate decreased slightly when the temperature exceeded 35°C.…”
Section: Biomassmentioning
confidence: 71%
“…The change of dry cell weight depending on temperature increase for L. brevis ED25 was higher than that of other strains. The study was supported by Simonson, Salovaara, and Korhola (2003) and Hassani, Zarnkow, and Becker (2015) who reported that the bacterial cell concentration increased significantly with the increase of the fermentation temperature. A partial decrease of dry cell weight for L. curvatus N19 was observed after fermentation of 25h and at temperature after 29.5 o C. Similarly, Zhou, Zeng, Han, and Liu (2015) stated that the cell growth rate was significantly influenced by fermentation temperature, but the growth rate decreased slightly when the temperature exceeded 35°C.…”
Section: Biomassmentioning
confidence: 71%
“…100 mL or gram of a product containing around 7 log10 cfu mL À1 viable cells (Gomes & Malcata, 1999;De Vuyst, 2000). As indicated in the study of Hassani et al (2015), the fermentation of sorghum wort with the probiotic lactobacillus acidophilus LA5 resulted in 8 log10 cfu mL À1 viable cells. All studied fermentation parameters i.e.…”
Section: Probiotication Of Cereal-based Media By Applying Lactic Acidmentioning
confidence: 90%
“…As indicated in the study of Hassani et al . (), the fermentation of sorghum wort with the probiotic lactobacillus acidophilus LA5 resulted in 8 log10 cfu mL −1 viable cells. All studied fermentation parameters i.e.…”
Section: Accumulation Of Functional Bioactive Components By Fermentatmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional method for optimisation of medium conditions involves the 'one-factor-at-a-time' method, which is time-consuming and often fails to reflect the interaction among different parameters (Charyulu & Gnanamani, 2010). However, response surface methodology (RSM), which can eliminate the disadvantages of the traditional method, has been proved to be powerful and effective to optimise cultivation process (Wang et al, 2013;Hassani et al, 2015).…”
Section: Introductionmentioning
confidence: 99%